Exploring change in a group-based psychological intervention for multiple sclerosis patients. Issue 14 (3rd July 2018) - Borghi, Martina; Bonino, Silvia; Graziano, Federica; Calandri, Emanuela
Abstract: Purpose: The study is focused on a group-based cognitive behavioral intervention aimed at promoting the quality of life and psychological well-being of multiple sclerosis patients. The study investigates how the group intervention promoted change among participants and fostered their adjustment to the illness. Materials and methods: The intervention involved six groups of patients (a total of 41 patients) and included four consecutive sessions and a 6-month follow-up. To explore change, verbatim transcripts of the intervention sessions were analyzed using a mixed-methods content analysis with qualitative data combined with descriptive statistics. The categories of resistance and openness to change were used to describe the process of change. Results: Resistance and openness to change coexisted during the intervention. Only in the first session did resistance prevail over openness to change; thereafter, openness to change gradually increased and stabilized over time, and openness to change was then always stronger than resistance. Conclusions: The study builds on previous research on the effectiveness of group-based psychological interventions for multiple sclerosis patients and gives methodological and clinical suggestions to health care professionals working with multiple sclerosis patients. Implications for rehabilitation: The study suggests that a group-based cognitive behavioral intervention for multiple sclerosis patients focused on the promotion of identity redefinition, a sense of coherence and self-efficacy in dealing with multiple sclerosis fosters the process of change and may be effective in promoting patients' adjustment to their illness. Health care professionals leading group-based psychological interventions for multiple sclerosis patients should be aware that resistance and openness to change coexist in the process of change. The study suggests that the duration of the intervention is a crucial factor: a minimum of three sessions appears to be necessary for group participants to develop greater openness to change and follow-up sessions should be implemented to maintain positive changes among participants. The use of qualitative instruments to evaluate group interventions captures the complexity of processes and gives useful indications to health professionals to improve rehabilitation programs.